INOVASI DIGITALISASI PEMBELAJARAN BAHASA DI ERA PENDIDIKAN MODERN - Jaya, Aswadi; Pratama, Aldora (Universitas PGRI Palembang, 2024)
Digital learning innovation in the modern educational era has become a crucial factor in enhancing the quality of education and addressing the challenges faced by the current educational system. This study aims to explore the benefits, challenges, and implications of digital-based learning, particularly in the context of education in Indonesia. Through a literature review method, this research collects and analyzes information from various literature sources, including books, scholarly articles, and official documents. The findings indicate that digital learning provides broader access for students, especially in remote areas, and can enrich their learning experiences. However, challenges such as limited technological infrastructure and the need for teacher training must be addressed to optimize the implementation of digital learning. Therefore, it is essential for all stakeholders to collaborate in developing effective strategies for the implementation of digital learning innovations. This research is expected to contribute to the development of education in Indonesia and serve as a reference for future studies.